OBSERVATIONS ON SEX PROPORTIONS AND MATURITY TRENDS IN CYNOGLOSSUS BILINEATUS (LACEPEDE) AND C. MACROLEPIDOTUS (BLEEKER) AT CALICUT DURING 1968-73 - Seshappa, G (Indian Journal of Fisheries, 2011)
Occasional specimens of C. macrolepidotus and C. bilineatus noticed in random sample’s of the iMalabar sole were examined from 1968 to 1973. Males, females and indetenminates formed 30.1%, 34.2% and 14.0%, respectively, in C. macrolepidotus and 45.0%, 44.0% and 5.0%, respectively, in C. bilineatus. In the former species, 95.2% of the females were in stage I while only 1% were in stage IM, 4% in stage IV and nil in other maturity stages. In the latter species 70.5% of the females were in stage I, 4.6% each-in stages HI and V, 6.8% in stage 11 and 12.5% in stage IV.